PERAN GANDA WANITA PEDAGANG DI PASAR BERSEHATI KELURAHAN CALACA KECAMATAN WENANG KOTA MANADO (Studi Kasus Tentang Peran Seorang Ibu Menjadi Kepala Rumah Tangga dalam Mencari Nafkah) - Tumiwa, Juliana; Kandowangko, Nicolas; Kalele, Jureine Valentin Debora (Universitas Sam Ratulangi, 2019)
Father as the head of the household therefore he must take full responsibility in the form of protecting the family and make a living for the needs of the family. While a mother is a housewife who does not have to support the family, it is also not forbidden to work if given permission.The phenomenon that occurs in society is the increasing number of women to assist in earning a living, as well as being driven by the needs of a little family economy, women are increasingly able to express themselves in the midst of families and Community.A mother with a trader has a double role. This role in addition to being a coaching in the family to work hard but also sustain economic life in the family.A qualitative study method based on the philosophy of post positivism or interpretive, is a naturalistic, qualitative method of research in which the process is inductive.In the activity as a merchant mother does not diminish her role as a mother in the household, such as taking care of the house and family despite the time to trade but them still run the responsibility well. Because also the job of the trader is not tied, so they have set their time to be able to socialize with the community around the house such as the Association of worship p, especially taking time for family events.Keywords: housewife, family, trader